2017
DOI: 10.1158/1535-7163.mct-16-0552
|View full text |Cite
|
Sign up to set email alerts
|

Co-targeting HGF/cMET Signaling with MEK Inhibitors in Metastatic Uveal Melanoma

Abstract: Metastatic uveal melanoma (UM) patients usually die within one year of diagnosis, emphasizing an urgent need to develop new treatment strategies. The liver is the most common site of metastasis. Mitogen-activated protein kinase kinase (MEK) inhibitors improve survival in V600 BRAF-mutated cutaneous melanoma patients but have limited efficacy in UM patients. Our previous work showed that HGF signaling elicits resistance to MEK inhibitors in metastatic UM. In this study, we demonstrate that expression of two BH3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 46 publications
3
65
0
Order By: Relevance
“…In addition, our findings indicated that stromal FGF2 rescues BET inhibitor effects in metastatic UM cells and also showed upregulation of FGFR expression as an adaptive response to BET inhibitors in cell lines and patient tumor samples. Previously, we reported that HGF secreted from HSCs rescued metastatic UM cells from the growth inhibitory effects of a MEK inhibitor, trametinib, and was associated with paracrine activation of cMET and PI3K/AKT pathways (Cheng et al, 2015(Cheng et al, , 2017. Our findings highlight the ability of stromal cells in the TME to mediate resistance to targeted inhibitors in UM.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, our findings indicated that stromal FGF2 rescues BET inhibitor effects in metastatic UM cells and also showed upregulation of FGFR expression as an adaptive response to BET inhibitors in cell lines and patient tumor samples. Previously, we reported that HGF secreted from HSCs rescued metastatic UM cells from the growth inhibitory effects of a MEK inhibitor, trametinib, and was associated with paracrine activation of cMET and PI3K/AKT pathways (Cheng et al, 2015(Cheng et al, , 2017. Our findings highlight the ability of stromal cells in the TME to mediate resistance to targeted inhibitors in UM.…”
Section: Discussionsupporting
confidence: 55%
“…Hepatocyte growth factor (HGF) provided resistance to trametinib growth inhibitory effects in metastatic UM cell lines and targeting of cMET (the receptor for HGF) enhanced the effects of trametinib in metastatic UM (40, 46). HGF-CMET signaling induced downregulation of BH3 pro-apoptotic proteins, BIM and BMF, which correlated with HGF-mediated inhibition of apoptosis in trametinib-treated cultures (46).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocyte growth factor (HGF) provided resistance to trametinib growth inhibitory effects in metastatic UM cell lines and targeting of cMET (the receptor for HGF) enhanced the effects of trametinib in metastatic UM (40, 46). HGF-CMET signaling induced downregulation of BH3 pro-apoptotic proteins, BIM and BMF, which correlated with HGF-mediated inhibition of apoptosis in trametinib-treated cultures (46). Importantly, HGF is secreted by quiescent hepatic stellate cells that can be found in the liver microenvironment and phosphorylated/activated cMET is detected in the majority of UM liver metastases (40, 46).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations